Interioridade e conhecimento em Agostinho de Hipona - Fernandes, Maria Imaculada Azevedo (2007)
This work has as a purpose to research the question of Augustin interiority through the problem of the knowledge. Both interiority and knowledge represent the key-pieces of Augustin thought and they bring an enigma which we ll be busy in understanding. It refers to the apparently antagonistic form to conciliate the human activity of the knowledge through the cogito of Augustin with the theory of the divine illumination. We ll research which is the statute of knowledge in Augustin thought; what it implies to say that the interiority is, at the same time, the place of the knowledge and the way to God; and if it is possible to conceive the knowledge as a function of the human intellect and an intuition of the contents of ideas coming from God